The Relationship between Changes in Nutrition Status and Length of Hospitalization in Patients in Department of Internal Medicine at University of Sumatera Utara Hospital - Lubis, Nenni Dwi Aprianti; Sianturi, Chaca Theresia; Balatif, Ridwan (Universitas Muhammadiyah Sumatera Utara, 2021)
The nutritional status of patients is one factor that influences the length of stay. This study is an analytic study with a cross-sectional design aiming to observe nutritional status, length of treatment, and the relationship between the two variables. The population in this study were patients aged 19-64 years who were treated in the Internal Medicine KSM at USU Hospital in the period August to October 2019. 52 patients were the study samples, with consecutive sampling as the sample selection technique used. We collected research data as nutritional status and length of stay through anthropometric measurements and structured interviews. We distinguish nutritional status based on Body Mass Index (BMI) and Subjective Global Assessment (SGA). The results showed 34 patients (65.4%) based on BMI values decreased nutritional status from 21.473.79 to 21.183.83 Kg /m2. Based on SGA, 32 patients (61.5%) experienced a decrease in score. The mean treatment period was 5.021.36 days. From the chi-square test results, it is known that changes in nutritional status based on BMI have a significant relationship to the length of stay with a p-value 0.05.